Anatomy and Pollination of Cleistogamous Flowers of Benghal Dayflower (Commelina benghalensis). Issue 3 (September 2016) - Hayden, W. John; Fagan, Camille
Abstract : The anatomy and pollination of subterranean cleistogamous flowers of Benghal dayflower ( Commelina benghalensis ) is described as a contribution to understanding its reproductive biology. Subterranean stems bear one spathe per node, each enclosing a single cleistogamous flower. Only the three anterior stamens produce functional pollen; the posterior three stamens are staminodes. Tapetum is amoeboid and endothecium is present. The three-carpellate superior ovary bears five dimorphic orthotropous ovules. Nearly mature flowers have straight to somewhat curved styles; at maturity, styles elongate and coil. Our observations indicate that coiled style growth causes rupture of anthers and brings pollen into contact with stigmas. Pollen tubes were observed in styles that had previously undergone coiling, located within mucilaginous secretions of the mature stylar canal. The subterranean cleistogamous flowers of Benghal dayflower and their apparently unique mode of pollination, viewed together with reproductive capacity of its aerial chasmogamous flowers, underscore the complexity and flexibility of the reproductive biology of this noxious weed species.